1992
DOI: 10.1093/genetics/131.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid recombination in a rad52 mutant of Saccharomyces cerevisiae.

Abstract: Using plasmids capable of undergoing intramolecular recombination, we have compared the rates and the molecular outcomes of recombination events in a wild-type and a rad52 strain of Saccharomyces cerevisiae. The plasmids contain his3 heteroalleles oriented in either an inverted or a direct repeat. Inverted repeat plasmids recombine approximately 20-fold less frequently in the mutant than in the wild-type strain. Most events from both cell types have continuous coconversion tracts extending along one of the hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…studies also showed the absence of intermolecular recombination between circular plasmids in the rad52 cells (10,15). This contrasts with the intramolecular direct-repeat DSB repair process, which is only partially RAD52 dependent.…”
Section: Resultsmentioning
confidence: 93%
“…studies also showed the absence of intermolecular recombination between circular plasmids in the rad52 cells (10,15). This contrasts with the intramolecular direct-repeat DSB repair process, which is only partially RAD52 dependent.…”
Section: Resultsmentioning
confidence: 93%
“…In S. cerevisiae, plasmids containing direct repeat are known to be unstable due to intraplasmid direct repeat recombination leading to loss of DNA between the repeats (20). Accordingly, plasmids supporting a multigene pathway such as BGLS biosynthesis may be prone to gene loss if some of the genes are equipped with the same promoter and terminator.…”
Section: Discussionmentioning
confidence: 99%